Selected breeding parameters of Jackdaw "Corvus monedula" in nesting boxes in Sulechów (Western Poland) - Czechowski, Paweł; Kurzaj, Michał; Jerzak, Leszek (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The paper presents selected parameters such as the number of eggs, egg size, number of fledglings and nesting success of Jackdaw "Corvus monedula" in nesting boxes. In February 2005, 35 nest boxes were hung on trees in a park in Sulechow, a town in Western Poland. Observations were conducted over the period 2005-2009. In each of the years the boxes were inhabited by 8, 15, 22, 11 and 6 pairs of Jackdaws, respectively.
Keywords: Jackdaw; Corvus monedula; breeding biology; nesting boxes; Sulechów; Poland